Relationships between the Visual Evaluation of Soil Structure (VESS) and soil properties in agriculture: A meta-analysis (Scientia Agropecuaria, 2023)
The aim of this study was to analyze the relationships between the Visual Evaluation of Soil Structure (VESS) and soil properties that make its adoption widely used in agriculture. For this, 25 papers related to the VESS (2009-2022) were considered, and information on the soil property: bulk density (BD), total soil porosity (TP), soil penetration resistance (PR), macroporosity, microporosity, soil organic carbon (SOC), and mean weight diameter of stable aggregates (MWD). The sample size (n=120 cases), and the correlation coefficient were extracted. A meta-analysis was carried out to obtain a global measure of the correlation between the VESS and soil properties. In the first instance, a fixed effects model was fitted for the correlation (effect size as the response variable in the meta-analysis). Subsequently, a random effects model was fitted for the correlation, followed by a subgroup analysis according to soil properties, due to the presence of high heterogeneity. The overall effect (average correlation coefficient) of the fitted random effects model was 0.31 with a confidence interval of 0.22-0.41. The heterogeneity between studies was high (I 2: 94%) and statistically significant (p